A note on recent studies of Acheulian assemblages in the Wainganga River Basin, India. (30th November 2021) - Joshi, Prachi
Abstract: This paper addresses ongoing work on the Palaeolithic archaeology of the Wainganga basin, Central India, focusing on investigating the nature of the occupation, technological changes, and transitions through time, with a view towards understanding Palaeolithic behaviour. Surveys conducted over an area of 19, 696 sq. km in this region, led to the discovery of 30 sites of the Acheulian and Late Palaeolithic with sparse evidence, as yet of the Middle Palaeolithic. Acheulian sites are deeply stratified within regoliths, but owing to recent exposures, several sites could be investigated in detail. This paper addresses preliminary research at a few of the Acheulian sites in this region, establishing their stratigraphic context and lithic assemblage structure. The assemblages studied suggest deliberate choices in the selection of raw materials involving the transport of tools/flakes for more than 15 km to specific sites where they were used. This is reflected by the absence of giant cores and sparse waste products at several sites studied. There is a preference for cleavers and the use of Kombewa technologies. The paper discusses the technological aspects of the assemblages and the importance of studying micro-regions when investigating broader patterns of hominin behavioral changes in the South Asian Acheulian.